Breast self examination and survival from breast cancer. - Le Geyte, M; Mant, D; Vessey, M; Jones, L; Yudkin, P (1992)
The survival of 616 women aged 15-59 with breast cancer, 226 of whom had been taught and practised breast self examination (BSE) prior to diagnosis and 390 of whom had not, is reported. Six year survival rates were 73.1% in the BSE taught group and 66.1% in other women (P = 0.07).